Evaluation of chlorpyrifos 50% + cypermethrin 5% EC against lepidopteran defoliators Helicoverpa armigera L. and Spodoptera litura L. on soybean: Evaluation of chlorpyrifos 50% + cypermethrin 5% EC against lepidopteran defoliators Helicoverpa armigera L. and Spodoptera litura L. on soybean - J B BHUT; A M BHARADIYA; R B MADARIYA (Journal of Oilseeds Research, 2023)
Field experiments on evaluation of chlorpyrifos 50% + cypermethrin 5% EC against lepidopteran defoliators H. armigera L.and S. litura L.on soybeanwas carried out at Main Oilseeds Research Station, Junagadh Agricultural University, Junagadh during kharif 2018 and 2019. All the treatments were significantly superior over untreated check. The pooled results of 5 and 10 days after spray indicated that lowest number of larvae/plant was recorded in the treatment of chlorpyrifos 50% + cypermethrin 5% EC 625 + 62.5 a.i./ha which was statistically at par chlorpyrifos 50% + cypermethrin 5% EC500+50 a.i./ha. Looking to the yield both treatments recorded 1818 and 1735 kg/ha, respectively.